Permanently Progressing? Building Secure Futures for Children in Scotland: Linking two national datasets about looked after children in Scotland to enhance understanding of pathways to permanence - Hooper, Jade; Cusworth, Linda; Whincup, Helen (International Journal of Population Data Science, 2018)
Background Permanently Progressing? is the first cohort study in Scotland aimed at understanding the factors associated with achieving settled and secure permanent homes for children. One part of this study involves analysing the national Children Looked After Statistics (CLAS) collected by the Scottish Government, to follow a group of children who became ‘looked after’ or ‘looked after and accommodated’ aged five or under. However, important decisions about these children are made at Children’s Hearings and the information about these decisions is stored in a database collated by the Scottish Children’s Reporters Administration (SCRA). Objectives As these two datasets have never before been linked, the researchers aim to test the feasibility and success of this linkage. In addition, analysis of the linked dataset will allow both a description of the pathways of children who became looked after in 2012-13, and a comparison of the pathways for children who have achieved permanence at the end of year 4 to those who are on a pathway to permanence, and those still accommodated with no evident permanence plan. Methods In this project, the anonymised CLAS data obtained from the Scottish Government are being brought together with anonymised data held by SCRA, using probabilistic linkage methodologies. Findings The linkage and analysis of this data is currently underway and will be discussed during this presentation. Conclusions If successful, this linkage will serve as a pilot study for future research, help inform policy and practice, and enable the researchers to gain a more in-depth picture of a child’s journey through the system and the factors associated with children achieving permanence. The success of this linkage and challenges encountered will be discussed.